Inmunidad antitumoral en neoplasias intraoculares - Urzúa S., Cristhian A.; López N., Mercedes; Pardo Q., Andrea; Ribeiro D., Ana Adélia; Tempio S., Fabián; Abuauad A., Sergio; Vásquez Z., Darío H. (Revista Hospital Clínico Universidad de Chile, 2013)
A physiological function of the immune system is to recognize and destroy cells transformed clones before they become tumors and eliminate tumors after they are formed. This is accomplished by innate and adaptive immune responses, however is a complex taskconsidering the mechanisms of evasion by tumors. Particularly, intraocular neoplasms (ION) would have an advantage against the immune system because the eye is considered a site of immune privilege that through anatomical, physiological and immunoregulatory mechanisms restrict the immune response. Regulatory T lymphocytes(Treg) subtype CD4 + CD25 + Foxp3 + and IL-10 producers, would be crucial in induction of self-tolerance .The loss of balance between proinflammatory profile given by LTh1 and LTh17 and its production of IFN-g and IL-17 versus the modulating function of Treg secreting IL-10 and TGF-β determines a faster tumor growth or not. There is still no conclusive evidence determining the specific mechanisms of immune imbalance in the ION. In this review we updated an overview of antitumor immunity, its particularities to intraocular level and current evidence about echanisms of immune evasion in most common primary malignant ION in adults: uveal melanoma and primary intraocular lymphoma.